Retained Placenta Creta After Selective Fetal Reduction in Twin Pregnancy: A Case Report. Issue 4 (13th October 2021) - Zheng, Weiran; Yang, Xinrui; Zhu, Yuchun; Yan, Jie; Yang, Huixia
Abstract : Abstract: Placenta accreta spectrum (PAS) disorders are severe obstetric complications and can cause life-threatening hemorrhage, hysterectomy, or even death. PAS disorders in one of dichorionic diamniotic twins are rare to be seen in clinical practice and lack of standard management strategies. We reported a case of retained placenta creta after selective fetal reduction in one of dichorionic diamniotic twins. A 32-year-old woman with a history of cesarean section was diagnosed with placenta increta in one of dichorionic diamniotic twins at 16 weeks of gestation. After discussion, the couple required to be hospitalized for selective fetal reduction. She received selective termination by ultrasound-guided single fetal intracardiac injection of potassium chloride. The follow-up prenatal ultrasound examinations detected the placenta of the reduced fetus did not stop invade the myometrium of the uterus but developed from placenta increta to placenta percreta. The patient was diagnosed with placental percreta by prenatal ultrasound signs and surgical findings. The patient underwent scheduled cesarean delivery at 34 +5 gestational weeks. The outcome of maternal and fetal was satisfactory for our elaborate operation and optimal management. PAS disorders are severe obstetric complications with an increasing incidence. Combined with twin pregnancy makes PAS disorders more intractable. We should learn that selective fetal reduction probably cannot solve it thoroughly. Intensive and standard management is essential to promote maternal and fetal outcomes.